Relationship between suicide probability and comorbid depression, anxiety, and personality disorders in alcohol dependence - Çelik, Seda; Demirbaş, Hatice; Özgür İlhan, İnci; Doğan, Yıldırım B. (Journal of Dependence, 2002)
Objective: Suicide and comorbid mental disorders are situations which are frenquently seen in alcohol dependency. The aim of this study is to determine the relationship between comorbid mental disorders and a number of variables as well as predictive power of various factors related to comorbid mental disorders on suicidal behavior in alcoholic inpatients.Method: Seventy alcoholic inpatients being treated in Alcohol and Substance Abuse Treatment Unit were included in this study. Comorbid mental disorder has been evaluated at the end of clinical observations and interview. Suicide risk has been detected with Suicide Probability Scale. In addition Beck Depression Inventory, Coopersmith Self-Esteem Inventory, Spielberger StateTrait Anxiety Scale have been used. For analysis of data, logistic regression analysis and t-test methods have been applied.Results: There is a direct and significant relationship between suicide probability and comorbid mental disorders. Thus 18 % of suicide probability can be explained by presence of comorbid mental disorders. There is a significant relationship between comorbid mental disorders and both depression and state anxiety. No statistically significant difference has been detected between patients with regard to presence or absence of history of either severe trauma or physical disease while being drunk.Conclusion: Diagnostic evaluation in alcohol dependence should be made taking in to consideration that comorbid mental disorders can indicate increased risk of suicide, so should the treatment plan be made accordingly.
Keywords: Alcohol dependence; comorbid mental disorders; suicide probability